Useful work v. useless toil - Morris, William (London Penguin Books, 2008)
Visionary English Socialist and pioneer of the Arts and Crafts movement, William Morris argued that all work should be a source of pride and satisfaction, and that everyone should be entitled to beautiful surroundings ? no matter what their class. Throughout history, some books have changed the world. They have transformed the way we see ourselves ? and each other. They have inspired debate, dissent, war and revolution. They have enlightened, outraged, provoked and comforted. They have enriched lives ? and destroyed them. Now Penguin brings you the works of the great thinkers, pioneers, radicals and visionaries whose ideas shook civilization and helped make us who we are.